Factors Influencing the Capital Adequacy Ratio : A Panel Regression Analysis for the Vietnamese Banking Sector - Tran, Linh Thi Thuy; Pham, An Ha Thi (Indian Journal of Finance, 2022)
Currently, commercial banks are constantly implementing measures of capital adequacy to meet Basel standards. Commercial banks mainly issue bonds to increase their tier 2 capital and mobilize long-term capital for lending needs and capital adequacy. Therefore, this study aimed to determine the internal and macro factors affecting Vietnamese commercial banks’ capital adequacy from 2007 – 2018. Applying the feasible generalized least squares (FGLS) estimator, our results showed that return on equity (ROE) and bank size (SIZE) had the significantly opposite impact on Vietnamese banks’ capital adequacy. However, return on assets (ROA), customer deposits (DEP), credit risk (CR), and liquidity (LIQ) had similar direction effects and were statistically significant on banks’ capital adequacy. For the macroeconomic factors, the inflation rate positively impacted the capital adequacy of Vietnamese commercial banks. Besides, our results revealed that Vietnamese commercial banks need to control internal factors and improve their performance to ensure capital adequacy according to Basel standards in globalization.